The Nup358-RanGAP complex is required for efficient importin α/β-dependent nuclear import - Hutten, Saskia; Flotho, Annette; Melchior, Frauke; Kehlenbach, Ralph H. (Molecular biology of the cell, 2008)
In vertebrate cells, the nucleoporin Nup358/RanBP2 is a major component of the filaments that emanate from the nuclear pore complex into the cytoplasm. Nup358 forms a complex with SUMOylated RanGAP1, the GTPase activating protein for Ran. RanGAP1 plays a pivotal role in the establishment of a RanGTP gradient across the nuclear envelope and, hence, in the majority of nucleocytoplasmic transport pathways. Here, we investigate the roles of the Nup358-RanGAP1 complex and of soluble RanGAP1 in nuclear protein transport, combining in vivo and in vitro approaches. Depletion of Nup358 by RNA interference led to a clear reduction of importin α/β-dependent nuclear import of various reporter proteins. In vitro, transport could be partially restored by the addition of importin β, RanBP1, and/or RanGAP1 to the transport reaction. In intact Nup358-depleted cells, overexpression of importin β strongly stimulated nuclear import, demonstrating that the transport receptor is the most rate-limiting factor at reduced Nup358-concentrations. As an alternative approach, we used antibody-inhibition experiments. Antibodies against RanGAP1 inhibited the enzymatic activity of soluble and nuclear pore-associated RanGAP1, as well as nuclear import and export. Although export could be fully restored by soluble RanGAP, import was only partially rescued. Together, these data suggest a dual function of the Nup358-RanGAP1 complex as a coordinator of importin β recycling and reformation of novel import complexes.